Tunable Multilevel Gate Oxide Capacitance and Flat‐Band Voltage Shift Characteristics by Filament Formation in Double‐Floating‐Gate Metal–Oxide–Semiconductor Capacitors (Adv. Electron. Mater. 4/2023). (11th April 2023) - Han, Jimin; Park, Kitae; Kim, Hyun‐Mi; Yoon, Tae‐Sik
Abstract : Metal–Oxide–Semiconductors In article number 2201110 by Tae‐Sik Yoon and coworkers, a tunable multilevel gate oxide capacitance and flat‐band voltage shift characteristics in double‐floating‐gate metal‐oxidesemiconductor capacitors are demonstrated as operating with both conducting filament formation and electrical charging in the gate stack, depending on the constituent materials and device geometries. It paves the way for the potential application to non‐volatile memory and programmable logic devices.